EVIDENCE OF EXPORT LED GROWTH (ELG) HYPOTHESIS THEORY IN INDIAN MANUFACTURING SECTOR AND A SOURCE OF FDI - Dr. V. Gajapathy; Uma Chinchane (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The highly discussed topic among the economists from the last 2 decades, is the association between Exports, Economic growth and Foreign Direct Investment. Many economists have claimed that the growth in exports have a dominant role played in improving economies of scale, reaching new markets, innovations, and thus in attracting capital. There are studies which support the relationship between the increase in Export attracting Capital. Export Led Growth Hypothesis (ELGH) is a theory which supports the impression of Exports in Economic growth. This study is a work done to verify the same ELGH theory for Indian Economy. The study has been conducted for a period of 1998 to 2018 and using simple linear regression model, we have been able to find the significant influence of Exports on growth of economy. The key manufacturing sectors contributing to GDP have been identified and the need for policy frameworks, and focus required on specific manufacturing sectors have been identified. The study further aims at finding a relationship between the exports and FDI in India.